Upgrading Chinese Shengli lignite by microwave irradiation for slurribility improvement. (1st November 2015) - Zhou, Fan; Cheng, Jun; Wang, Aiying; Liu, Jianzhong; Zhou, Junhu; Cen, Kefa
Abstract: Shengli lignite with high moisture content from the Inner Mongolia region of China was upgraded by microwave irradiation to prepare high-quality coal water slurry (CWS) fuel for combustion and gasification. The physicochemical properties of the upgraded lignite on the as-received basis were investigated with Fourier transform-infrared spectroscopy, X-ray diffraction spectroscopy, N2 adsorption porosimetry, scanning electron microscopy, contact angle analysis and rotary viscometry. Oxygen functional groups with high hydrophilicity decreased in the upgraded lignite. The decreased molar ratio of aliphatic hydrogen to aromatic hydrogen implied an increase in coalification degree. The particle size and contact angle of the upgraded lignite increased. When the upgraded lignite with a decreased hydrophilicity index was used to prepare CWS, the maximum solid concentration increased from 45.6 wt.% to 51.7 wt.%. Microwave irradiation was more efficient for removing external free moisture than internal bonded moisture in Shengli lignite. The unit energy consumption for external moisture removal and CWS concentration promotion was lower than that for internal moisture removal.